Global research trends on the relationship between gut microbiota and melanoma from 2014 to 2023: a bibliometric and visualization analysis - Liu, Sai; Hu, Kewang; Zhu, Mingli (Frontiers in Microbiology, 2025)
Melanoma, a type of malignant tumor, originates from skin cells known as melanocytes. The gut microbiota is closely linked to melanoma, and this bibliometric analysis aims to guide future studies and advance research into the role of the gut microbiome in melanoma. We used the Web of Science Core Collection database to identify relevant literature on the function of intestinal flora in melanoma from 2014–2023, and bibliometric analysis and network visualization were performed with VOSviewer, CiteSpace. A total of 886 articles were identified, with significant contributions from the United States, France, and China. The role of gut microbiota in the onset, progression, and treatment of melanoma is becoming increasingly clear, especially in its potential to improve immunotherapy outcomes. In conclusion, this research used bibliometric analysis to perform a thorough quantitative and qualitative evaluation of the literature concerning the role of gut microbiota in melanoma. Advancing research in this area offers hope for enhancing melanoma treatments by regulating the gut microbiome, which could lead to improved patient outcomes in the future.